Statistical modelling and evaluation of aircraft collision risk using correlation theory - Васильєв, В.М. (Proceedings of National Aviation University (archive), 2004)
The method of statistical modelling and evaluation of collision probability is offered. It can make a methodological basis for an evaluation of air traffic safety, and also to be applied to detection of potential conflict situations while air traffic control. For the mathematical description of predicted air traffic movement, and for the evaluation of collision probability the correlation functions of deviation process from planned flight trajectory are used. The procedure of an evaluation of collision risk is presented.